Kesetaraan Gender Di Area Kampus Universitas Jember - Adil Fihukmi Farqi; Yuzicha Nindia Safira Revizal; Tiara Putri Maulida (Pusat Riset dan Inovasi Nasional, 2023)
Women are often charged with housework which makes them less exposed to information regarding gender equality that occurs between men and women. For this reason, there needs to be awareness and feelings of mutual respect. Especially in the higher education environment, there is a need for campaigns or even courses that discuss gender equality. The aim of carrying out this research is none other than to find out whether gender equality has been implemented in the campus area, in other words in higher education. The research method applied and used in this research is descriptive qualitative using a critical discourse approach model. The results of the research show that the three informants said that maximum gender equality has not been implemented in the campus environment as evidenced by the large number of male leaders and the lack of access for women in terms of education and information. The conclusion is that gender equality is very important. To make this happen, it is necessary to carry out various actions such as campaigns and disseminating information through social media in order to raise awareness within each individual.